PENGARUH JOB INSECURITY TERHADAP TURNOVER INTENTION DIMEDIASI OLEH KEPUASAN KERJA PEGAWAI KONTRAK - Tisnawati, Ni Kadek Ayu; Satrya, I Gusti Bagus Honor (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p07, 2024)
This study aims to explore the impact of job uncertainty on the desire to change jobs which is influenced by job satisfaction. The research was conducted at the Department of Cooperatives, Small and Medium Enterprises, and Trade in Jembrana Regency, with a total of 124 employees, a sample of 100 contract/ASN employees was taken using a comprehensive sampling method. Data were collected through questionnaires, interview sessions, and observations. This study refers to social exchange theory and uses path analysis and classical assumption tests in analyzing data. The test found that job insecurity contributes positively and significantly to turnover intention, while job insecurity has a negative and significant impact on job satisfaction. In addition, job satisfaction also has a negative and significant impact on job change intention. Interestingly, this study also shows that job satisfaction acts as a mediator between job uncertainty and turnover intention. Therefore, it is recommended that related parties, such as the Cooperatives, SMEs, and Trade Office of Jembrana Regency, pay more attention to job stability and job satisfaction of employees to reduce the level of job switching intention in their environment.